Transport and climate change - Ryley, Tim; Chapman, Lee, 1977- (Transport and sustainability ;, 2012)
Transport accounts for 23% of global carbon dioxide emissions and is one of the few industrial sectors where emissions are still growing. There is a pressing need for transport to begin reducing emissions to mitigate the impacts of climate change. The world is already committed to some degree of climate change and there is an additional need to adapt transport networks to cope with the future climate. This book examines the relationship between transport and climate change at a range of scales and from a series of different perspectives. The complex post-Kyoto international situation is covered before the discussion at national and then regional levels. It is clear that every country needs strong national policy to deliver the required greenhouse gas emission reductions. The UK has been the first country to implement a legally binding agreement to reduce greenhouse gas emissions. This book uses a range of UK examples to provide a timely record of progress to date in meeting the demands of the agreement in terms of the mitigation of climate change. The importance of climate and socio-economic scenarios forms the basis of a series of additional discussions on climate change adaptation, underlining the need for a holistic framework to tackle climate change in the transport sector.